An Analysis of the Religious Solidarity Discourses Regarding the Syrian Refugees in Türkiye - Melih Çoban (Religions, 2024)
Following the outbreak of the civil war in Syria, a massive migration of Syrian nationals to Türkiye has been a significant phenomenon. This situation has become a problematic issue, as the massive presence of Syrian refugees in Türkiye has become an important part of the domestic political agenda. The politicization of the refugee issue has long since presented a duality of conflicting opinions among the Turkish society, whereas it has led to political debates between pro-government and opposition groups. In light of these developments, Turkish government elites have produced discourses of religious solidarity with the aim of providing tolerance and social acceptance for Syrian refugees and thus legitimizing the open door policy of the government toward these refugees. The aim of this study is to analyze and categorize the themes that constitute the basis of the discourses of religious solidarity regarding Syrian refugees in Türkiye. In this context, a second aim is to demonstrate how these themes have been welcomed in a positive manner by their adoption and recognition by Turkish society. To these aims, governmental discourses of religious solidarity and a sample consisting of 980 posts on the digital platform X have been analyzed by using the critical discourse analysis technique and have been categorized under two discursive themes, namely the ensar–muhacir analogy and the emphases on the Ottoman legacy. The conformity between these discourses and the government’s ideological orientation and the degree to which these discourses have been welcomed and adopted by the Turkish society have been discussed in detail.